Analisis Efektivitas Sistem Informasi Akuntansi Penggajian Karyawan Pada PT Golden Rooster Indonesia - sari, Meila (COMPETITIVE, 2021)
Payroll accounting information systems are very influential in a company system, namely the implementation of employee payroll and decision making in the company. The purpose of this study is to analyze the application and effectiveness of the existing payroll accounting system at PT Golden Rooster Indonesia whether the system run by the company is effective and efficient in carrying out employee payroll and can overcome problems that arise in the employee payroll system. The method used in this research is using qualitative research methods with a descriptive approach. The research uses primary and secondary data sources, namely by observation, interviews and documentation where after the data is obtained it will be reduced then the data presentation and finally conclusions are drawn from the formulation of the problems found and to get the results. The results showed that the payroll accounting information system at PT Golden Rooster Indonesia was running well, the payroll system was computerized so as to make the payroll process more effective and efficient.Keywords: Payroll Accounting Information System, Effectiveness, Employees.